Increasing drug resistance in extensively drug-resistant tuberculosis, South Africa. - Shah, N Sarita; Richardson, Jessica; Moodley, Prashini; Moodley, Salona; Babaria, Palav; Ramtahal, Melissa; Heysell, Scott K; Li, Xuan; Moll, Anthony P; Friedland, Gerald; Sturm, A Willem; Gandhi, Neel R (Emerging infectious diseases, 2011)
We expanded second-line tuberculosis (TB) drug susceptibility testing for extensively drug-resistant Mycobacterium tuberculosis isolates from South Africa. Of 19 patients with extensively drug-resistant TB identified during February 2008-April 2009, 13 (68%) had isolates resistant to all 8 drugs tested. This resistance leaves no effective treatment with available drugs in South Africa.
Keywords: Adult; Antitubercular Agents; Drug Resistance, Multiple, Bacterial; Extensively Drug-Resistant Tuberculosis; Female; Humans; Male; Microbial Sensitivity Tests; Middle Aged; Mycobacterium tuberculosis; South Africa; Tuberculosis, Multidrug-Resistant; Young Adult